What Drives Online Halal Food Purchasing Decisions? Evidence from Indonesian Muslim Consumers - Cupian Cupian; Agisty Aulia Trisnanda; Sarah Annisa Noven (Share: Jurnal Ekonomi dan Keuangan Islam, 2026)
The rapid expansion of e-commerce and digital consumption in Indonesia has transformed consumer purchasing behavior, including in the halal food sector. As one of the world’s largest Muslim-majority countries, Indonesia presents a unique context in which halal considerations intersect with digital information, online interaction, and brand reputation in shaping consumer decisions. This study examines the effects of halal awareness, information quality, and online reviews on purchasing decisions, with brand trust serving as a mediating variable, for Indomie instant noodle products purchased through the Shopee e-commerce platform among Muslim consumers in the Jabodetabek region. The study employed a quantitative research design using primary data collected through questionnaires distributed to 230 respondents. Responses were measured using a Likert scale and analyzed using Partial Least Squares–Structural Equation Modeling (PLS-SEM) with SmartPLS 4 software. The findings indicate that halal awareness does not significantly influence purchasing decisions or brand trust. In contrast, information quality and online reviews significantly and positively affect both purchasing decisions and brand trust. Brand trust also demonstrates a significant positive influence on purchasing decisions. Furthermore, brand trust mediates the relationships between information quality, online reviews, and purchasing decisions, but does not mediate the relationship between halal awareness and purchasing decisions. The study contributes to the growing literature on halal consumer behavior and digital commerce by demonstrating that, within the context of well-established halal-certified brands, online informational factors and consumer-generated content play a more dominant role in influencing purchasing decisions than halal awareness alone. ABSTRAK - Apa yang Mendorong Keputusan Pembelian Online Makanan Halal? Bukti dari Konsumen Muslim Indonesia. Perkembangan e-commerce dan konsumsi digital di Indonesia telah mengubah pola perilaku konsumen, termasuk dalam pembelian produk makanan halal. Sebagai negara dengan populasi Muslim terbesar di dunia, Indonesia menghadirkan konteks yang menarik ketika pertimbangan halal berinteraksi dengan kualitas informasi digital, ulasan konsumen, dan kepercayaan merek dalam memengaruhi keputusan pembelian. Penelitian ini bertujuan menganalisis pengaruh halal awareness, quality of information, dan online review terhadap keputusan pembelian dengan brand trust sebagai variabel mediasi pada produk mi instan Indomie melalui platform e-commerce Shopee di kalangan konsumen Muslim Jabodetabek. Penelitian menggunakan pendekatan kuantitatif dengan data primer yang diperoleh melalui penyebaran kuesioner kepada 230 responden. Pengukuran dilakukan menggunakan skala Likert dan dianalisis menggunakan metode Partial Least Squares–Structural Equation Modeling (PLS-SEM) dengan bantuan perangkat lunak SmartPLS 4. Hasil penelitian menunjukkan bahwa halal awareness tidak berpengaruh signifikan terhadap keputusan pembelian maupun brand trust. Sebaliknya, quality of information dan online review berpengaruh positif dan signifikan terhadap keputusan pembelian serta brand trust. Brand trust juga terbukti berpengaruh positif signifikan terhadap keputusan pembelian. Selain itu, brand trust mampu memediasi pengaruh quality of information dan online review terhadap keputusan pembelian, tetapi tidak memediasi pengaruh halal awareness terhadap keputusan pembelian. Penelitian ini memberikan kontribusi pada literatur perilaku konsumen halal dan perdagangan digital dengan menunjukkan bahwa pada merek halal yang telah mapan, faktor informasi digital dan ulasan konsumen memiliki pengaruh yang lebih dominan dibandingkan kesadaran halal dalam membentuk keputusan pembelian konsumen.